A survey of tourism management attitudes to renewable energy supply in Primorsko-Goranska County (Croatia) - Knežević, Rade (Array, 2008)
The paper presents the methodology of a conducted questionnaire survey and the results regarding energy consumption in the tourism of Primorsko-Goranska County (Croatia). The attitudes about energy consumption management and practical aspects concerning consumption are highlighted. The pool consists of three major groups of tourism objects: hotels and related facilities, camping parks and marinas. The plan was to analyze 91 tourism object, but only from 30 objects was achieved the response (33% rate). Largest share of the pool is located in the coastal area (73%), and much smaller shares are in the mountain region (13%) and the islands (13%). The results of analysis show that the largest amount of energy is used for interior heating/cooling (26,0%) and food purposes (24,5%), then for the illumination (17,3%), hot water (17,0%), laundering and ironing (10,4%), cleaning and waste disposal (2,6%) and other (2,1%). The attitudes about saving are emphasized and 96,7% of surveyed managers suppose that it is possible to manage the energy consumption and that energy increasingly influences their sustainable business activities. Information technology equipment for energy consumption control was installed in 16,7% of facilities and only 13,3% of businesses were exploiting renewable energy sources (RES) in 2007